Optimization of Landscape Services under Uncoordinated Management by Multiple Landowners - Porto, Miguel; Correia, Otilia; Beja, Pedro (PLOS ONE, 2014)
Landscapes are often patchworks of private properties, where composition and configuration patterns result from cumulative effects of the actions of multiple landowners. Securing the delivery of services in such multi-ownership landscapes is challenging, because it is difficult to assure tight compliance to spatially explicit management rules at the level of individual properties, which may hinder the conservation of critical landscape features. To deal with these constraints, a multi-objective simulation-optimization procedure was developed to select non-spatial management regimes that best meet landscape-level objectives, while accounting for uncoordinated and uncertain response of individual landowners to management rules. Optimization approximates the non-dominated Pareto frontier, combining a multi-objective genetic algorithm and a simulator that forecasts trends in landscape pattern as a function of management rules implemented annually by individual landowners. The procedure was demonstrated with a case study for the optimum scheduling of fuel treatments in cork oak forest landscapes, involving six objectives related to reducing management costs (1), reducing fire risk (3), and protecting biodiversity associated with mid-and late-successional understories (2). There was a trade-off between cost, fire risk and biodiversity objectives, that could be minimized by selecting management regimes involving ca. 60% of landowners clearing the understory at short intervals (around 5 years), and the remaining managing at long intervals (ca. 75 years) or not managing. The optimal management regimes produces a mosaic landscape dominated by stands with herbaceous and low shrub understories, but also with a satisfactory representation of old understories, that was favorable in terms of both fire risk and biodiversity. The simulation-optimization procedure presented can be extended to incorporate a wide range of landscape dynamic processes, management rules and quantifiable objectives. It may thus be adapted to other socio-ecological systems, particularly where specific patterns of landscape heterogeneity are to be maintained despite imperfect management by multiple landowners.
APS
Keywords: Biodiversity; Fire risk; fuel management; Landscape management; landwoners; socio-ecology

Forest fuel management as a conservation tool for early successional species under agricultural abandonment: The case of Mediterranean butterflies - Verdasca, Maria João; Leitão, Ana Sofia; Santana, Joana; Porto, Miguel; Dias, Susana; Beja, Pedro (Biological Conservation, 2012)
In cultural landscapes there are often negative biodiversity consequences of agricultural abandonment and subsequent scrub and forest encroachment, due to homogenization and the loss of early-successional habitats. The common forestry practice of removing understory vegetation to prevent ﬁre hazard (fuel management) probably has the side-effect of ameliorating these consequences, but it is uncertain whether it effectively restores habitats for early-successional species. Here we examine the inﬂuence of time since fuel management and management frequency on butterﬂy assemblages, using a chronosequence of cork oak (Quercus suber) stands spanning about 70 years. Overall species richness increased immediately after management and abundances peaked about 2–3 years later, while both declined thereafter for about 10–20 years to pre-disturbance levels. Richness and abundances were also much higher in recurrently managed stands. Most life history groups showed successional trends similar to the overall species richness and abundances, though consistent positive effects of fuel management were only observed for species with univoltine life cycle, herbaceous layer feeding, larval overwintering, and intermediate body size. Individual species were largely associated with recent and recurrent management, though a few specialists occurred most often in undisturbed stands. These ﬁndings suggest that fuel management at <10 years intervals is strongly positive for butterﬂy assemblages in landscapes under land abandonment. However, to maintain the overall forest biodiversity it is critical that patches of undisturbed habitat are also retained at the landscape scale.
Keywords: Disturbance ecology; Ecological succession; Forest management; Landscape mosaics; Mediterranean butterﬂy assemblages

Long-term responses of Mediterranean birds to forest fuel management - Santana, Joana; Porto, Miguel; Gordinho, Luís; Reino, Luís; Beja, Pedro (Journal of Applied Ecology, 2012)
1. Mechanical management of forest fuels is increasingly used in the Euro-Mediterranean region in response to the abandonment of traditional agroforestry and the concurrent increase in fire hazard. Although fuel management may have positive side effects for biodiversity, its long-term impacts remain largely unknown. 2. We used a 70-year post-management chronosequence to investigate the influence of time since fuel management and management frequency on bird assemblages in cork oak Quercus suber forests. 3. Fuel management strongly affected bird species richness, abundances and assemblage composition, with rapid changes often occurring during the first 10–20 years, followed in the next decades by a slow convergence to pre-management levels. 4. In winter, overall species richness and abundance, and that of frugivores and shrub foragers, were negatively affected by recent and recurrent management, only recovering in stands unmanaged for >50 years. In spring, insectivore abundance and the richness and abundance of shrub foragers declined immediately following management, increased to a maximum about 20 years later, and declined thereafter. Breeding granivores and ground foragers were the only groups that benefitted from fuel management. There were no overall effects on species of conservation concern, although a few species with unfavourable status benefitted from fuel management. 5. Synthesis and applications. Our study confirmed that mechanical fuel management has positive effects on some early-successional bird species of conservation concern, although its effects were limited. These benefits should be compared with the strong negative impacts on key bird species such as wintering frugivores, which play a pivotal role in ecosystems by promoting seed dispersal. To reconcile the positive and negative aspects, fuel management should be used to create heterogeneous mosaics of forest patches encompassing a range of sizes (10–100 ha) and successional stages of understorey vegetation, including stands undisturbed for >50 years. This management strategy will likely maintain conditions for a wide range of species with contrasting ecological requirements while also reducing fire hazard.
Keywords: Disturbance ecology; Ecological succession; Fire risk; Forest management; frugivores; Landscape mosaics; Mediterranean bird assemblages

Long-term consequences of mechanical fuel management for the conservation of Mediterranean forest herb communities - Porto, Miguel; Correia, Otilia; Beja, Pedro (Biodiversity and Conservation, 2011)
Mechanical clearing of understory vegetation is increasingly used in EuroMediterranean forests to reduce ﬁre hazard, yet its long-term consequences for biodiversity remain poorly understood. This study analysed the inﬂuence of time since understory management and management frequency, on herbaceous species richness, cover and composition, functional richness and composition, and richness and cover within functional groups (life and growth forms, dispersal strategy, clonality, and plant height), using a chronosequence of cork oak (Quercus suber) stands spanning about 70 years. Overall species richness was virtually constant over time, but the richness of species with annual life form and plasticity in height was much higher in recently and recurrently treated stands; the opposite was found for perennial (mainly hemicryptophytes and chamaephytes), tussock-forming and clonal species richness, and functional richness. Overall herbaceous cover and that of annual, semi-basal, non-clonal and plastic species (in height) were favoured by recent and recurrent fuel treatments; cover by perennial (hemicryptophytes and chamaephytes), short basal, tussock-forming, and clonal species tended to increase for[10–20 years after management, and declined with management frequency. There was a marked shift in species and functional composition associated with time since understory management and management frequency. These ﬁndings suggest that widespread fuel management at\10 year intervals may shift understory herb communities to early-successional stages, impairing the persistence of species and functional groups recovering slowly after disturbance. Fuel management needs to balance the dual goals of ﬁre hazard reduction and biodiversity conservation, retaining undisturbed patches in landscapes otherwise managed to reduce fuel accumulation.
Keywords: Disturbance ecology; Ecological succession; Forest management; Landscape mosaics; Mediterranean plant communities